Red meat consumption and risk for dyslipidaemia and inflammation: A systematic review and meta-analysis - Sun, Le; Yuan, Jia-Lin; Chen, Qiu-Cen; Xiao, Wen-Kang; Ma, Gui-Ping; Liang, Jia-Hua; Chen, Xiao-Kun; Wang, Song; Zhou, Xiao-Xiong; Wu, Hui; Hong, Chuang-Xiong (Frontiers in Cardiovascular Medicine, 2022)
Aim:The study (PROSPERO: CRD42021240905) aims to reveal the relationships among red meat, serum lipids and inflammatory biomarkers. Methods and Results: PubMed, EMBASE and the Cochrane databases were explored through December 2021 to identify 574 studies about red meat and serum lipids markers including total cholesterol (TC), triglyceride (TG), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), C-reactive protein (CRP) or hypersensitive-CRP (hs-CRP). Finally, 20 randomized controlled trials (RCTs) involving 1001 people were included , red meat and serum lipid markers and their relevant information was extracted. The pooled standard mean difference (SMD) was obtained by applying a random-effects model, and subgroup analyses and meta-regression were employed to explain the heterogeneity. Compared with white meat or grain diets, the gross results showed that the consumption of red meat increased serum lipid concentrations like TG (0.29 mmol/L, 95% CI 0.14, 0.44，P＜0.001), but did not significantly influence the TC (0.13 mmol/L, 95% CI -0.07, 0.33, P=0.21), LDL-C (0.11 mmol/L, 95% CI -0.23, 0.45, P=0.53), HDL-C (-0.07 mmol/L, 95% CI -0.31, 0.17,P=0.57),CRP or hs-CRP (0.13mmol/L, 95% CI -0.10, 0.37,P=0.273). Conclusions : Our study provided evidence to the fact that red meat consumption affected serum lipids levels like TG , but almost had no effect on TC, LDL-C,HDL-C and CRP or hs-CRP. Such diets with red meat should be taken seriously to avoid the problem of high lipid profiles.